2021
DOI: 10.3389/fpsyt.2021.707543
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Inflammation and Post-traumatic Stress Disorder

Abstract: Background: Stress disorders, such as post-traumatic stress disorder (PTSD), are attracting much attention. However, the relationship between traumatic stress and inflammation is rarely discussed.Subjects and Methods: As studies have linked PTSD to altered susceptibility to various diseases, such a psychiatric condition may lead to long-term systematic changes in physiological functions. We searched PubMed with the keywords “traumatic stress,” “stress disorders,” “post-traumatic stress disorder,” and “inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 62 publications
1
13
0
1
Order By: Relevance
“…Our data verified that MgH 2 was most likely to suppress anxiety/depression-like symptoms of EAE through modulating the inflammatory response rather than remyelination. Besides, these results, following the previous in-depth research on the neurobiological mechanism of depression, show that neuroinflammation plays an important role in the occurrence and development of depression [ 63 66 ].…”
Section: Discussionsupporting
confidence: 78%
“…Our data verified that MgH 2 was most likely to suppress anxiety/depression-like symptoms of EAE through modulating the inflammatory response rather than remyelination. Besides, these results, following the previous in-depth research on the neurobiological mechanism of depression, show that neuroinflammation plays an important role in the occurrence and development of depression [ 63 66 ].…”
Section: Discussionsupporting
confidence: 78%
“…Further, both preclinical and clinical studies have indicated an association between anxiety and immune regulation. [ 23 24 25 ] Increased levels of IL-6, a pro-inflammatory cytokine, are seen in anxiety, both in the periphery and brain. [ 26 27 ] In our present study, increased levels of IL-6 were seen after TDS in the PFC and hippocampus, in comparison to controls (no TDS) when compared to the control group, and pretreatment with WS lowered the elevated IL-6 levels seen in the experimental (V + TDS) group, in both brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Certain factors that may disrupt the homeostasis of the gut microbiome are likely to contribute to both immune-mediated inflammatory diseases and leaky gut syndrome [ 41 , 42 , 43 , 44 ]. Even though the mechanisms are not entirely clear, excess, uncontrolled psychological stress was shown to predispose patients to a subsequent development of systemic immune diseases and IBD as well [ 45 , 46 , 47 ]. Moreover, the clinical course of IBD often reflects the psychological state of patients; therefore, it seems plausible that, in certain circumstances, psychological interventions (e.g., cognitive behavioral therapy—CBD) may provide benefits for patients with IBD [ 48 ].…”
Section: Discussionmentioning
confidence: 99%